2016
DOI: 10.1021/acs.chemrestox.6b00187
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Tobacco Smoke Alters Metabolic Systems in Adult Rats

Abstract: Human exposure to environmental tobacco smoke (ETS) is associated with an increased incidence of pulmonary and cardiovascular disease and possibly lung cancer. Metabolomics can reveal changes in metabolic networks in organisms under different physio-pathological conditions. Our objective was to identify spatial and temporal metabolic alterations with acute and repeated subchronic ETS exposure to understand mechanisms by which ETS exposure may cause adverse physiological and structural changes in the pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…This differential dominance of these species among nonsmokers led significant minor upregulation of KEGG pathways involved in primary immunodeficiency which may increase the susceptibility to infections in smokers as supported by Ballow et al [ 34 ] that primary immunodeficiency is uncommon, chronic, and severe disorders of the immune system in which patients cannot mount a sufficiently protective immune response, leading to an increased susceptibility to infections. We also observed upregulation of citrate cycle, metabolism of Vitamin B6, butanoate, glycine, serine and threonine in smokers which has also been shown by Barupal et al, [ 35 ], where they reported that environmental tobacco smoke (ETS) exposure in adult rats shows adverse effects on the mitochondrial respiratory chain, lung elasticity, membrane integrity, redox states, cell cycle, and normal metabolic and physiological functions of lungs, even after subchronic ETS exposure. Further, alteration in metabolism of thiamine, D-glutamine and D-glutamate, D-arginine, and D-ornithine has also been earlier reported [ 36 ] and inhibition of pancreatic acinar mitochondrial thiamin pyrophosphate uptake by the cigarette smoke component 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone was suggested.…”
Section: Discussionsupporting
confidence: 85%
“…This differential dominance of these species among nonsmokers led significant minor upregulation of KEGG pathways involved in primary immunodeficiency which may increase the susceptibility to infections in smokers as supported by Ballow et al [ 34 ] that primary immunodeficiency is uncommon, chronic, and severe disorders of the immune system in which patients cannot mount a sufficiently protective immune response, leading to an increased susceptibility to infections. We also observed upregulation of citrate cycle, metabolism of Vitamin B6, butanoate, glycine, serine and threonine in smokers which has also been shown by Barupal et al, [ 35 ], where they reported that environmental tobacco smoke (ETS) exposure in adult rats shows adverse effects on the mitochondrial respiratory chain, lung elasticity, membrane integrity, redox states, cell cycle, and normal metabolic and physiological functions of lungs, even after subchronic ETS exposure. Further, alteration in metabolism of thiamine, D-glutamine and D-glutamate, D-arginine, and D-ornithine has also been earlier reported [ 36 ] and inhibition of pancreatic acinar mitochondrial thiamin pyrophosphate uptake by the cigarette smoke component 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone was suggested.…”
Section: Discussionsupporting
confidence: 85%
“…Compared to nonsmokers, primary basal stem/progenitor cells in the airways in healthy smoker had reduced metabolites in the tricarboxylic acid cycle, including acetyl-CoA, NADH, and FADH2 (Deeb et al, 2016). In contrast, an animal study has shown that CS exposure increased the levels of malate, citrate, and fumarate in rat lungs (Barupal et al, 2016). These studies suggest that CS may affect mitochondrial oxidative phosphorylation in a cell-specific manner.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolism produces energy and building blocks which are used for reproduction 5 , protection 6 , communication 7 , maintenance 8 and structure 9 of cells. Diseases, genetic and environmental factors interact with quantitative and qualitative changes in metabolism 10 12 . Understanding those changes and their biological effects on organism’s life is one of the basic questions of biology with importance ranging from synthetic biology to understanding the onset and progress of chronic diseases 13 .…”
Section: Introductionmentioning
confidence: 99%